Influence of soil N availability on the difference between tree foliage and soil δ15N from comparison of Mongolia and northern Japan. (June 2019) - Fujiyoshi, Lei; Sugimoto, Atsuko; Yamashita, Youhei; Li, Xiaoyang
Highlights: The difference between foliage and soil δ 15 N was investigated in Mongolia and Japan. In the two regions, Δδ 15 N varied similarly but the trend with soil δ 15 N was opposite. The variation of Δδ 15 N was explained by different process between the two regions. Soil N availability affects Δδ 15 N indicator owing to changes in the N cycle process. Abstract: Nitrogen isotope ratios (δ 15 N) in plants and soil are widely known as indicators of the N cycle in terrestrial ecosystem. Recent studies have proposed that the difference between plant and soil δ 15 N (Δδ 15 N) is a better indicator of the N cycle than plant δ 15 N or soil δ 15 N alone. However, the processes of the N cycle indicated by Δδ 15 N are not well understood. The present study compared Δδ 15 N variations between different ecosystems of northern Mongolia and northern Japan (Hokkaido) to associate the Δδ 15 N characteristics with soil N availability. Needles of Siberian larch ( Larix sibirica Ledeb.) in Mongolia, Todo-fir ( Abies sachalinensis (F.Schmidt) Mast.) in Hokkaido, and mineral soils from both regions were acquired for determination of Δδ 15 N values. Δδ 15 N showed similar large variations (8‰) in the two regions with no significant correlations to climate factors. On the other hand, the relationship between Δδ 15 N and soil δ 15 N was opposite between the two regions with a positive correlation in Mongolia ( rs  = 0.504) and a negative correlation in Hokkaido ( rs  = −0.600). Moreover, total inorganic N (total amount of NH4 + and NO3 − ) contents were up to 20 times higher in Hokkaido than in Mongolia. Δδ 15 N showed significant correlation with the fraction of NO3 − relative to total inorganic N in the 0–10 cm soil layer in Hokkaido. These results indicate that Δδ 15 N variation in Hokkaido can be explained by progression of nitrification in soil, which is different in Mongolia where Δδ 15 N variation is explained by microbial N immobilization. Our findings suggest that soil N availability affects Δδ 15 N indicator owing to changes in the N cycle process, which are reflected in the relationships of foliage δ 15 N or soil δ 15 N with Δδ 15 N.